Growing strong inside - Davis, Jennie; Hohag, Linda (Elgin, Ill. : Dandelion House ; Chicago, IL : Distributed by Childrens Press, 1985)
Suggests how a small child can grow in sharing, caring, and polite ways that show self-control.
Keywords: Children; Conduct of life